2005
DOI: 10.1158/0008-5472.can-05-0134
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for Galectin-7: Promoting Tumorigenesis by Up-regulatingMMP-9Gene Expression

Abstract: Metastasis is a multistep process by which cancer cells, after acquiring several capabilities, spread to distinct sites in the body. It is the major cause of death in individuals suffering from cancer. We have recently identified galectin-7 as a new gene associated with the progression of T cell lymphoma toward a metastatic phenotype, suggesting a possible causal relationship. The present study was designed to investigate the role of galectin-7 in lymphoma. We found that the development of thymic lymphoma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 35 publications
3
77
0
1
Order By: Relevance
“…These results, on the levels of production of mRNA and protein, pinpoint Galectin-1 as a potent inducer of extracellular presence of MMPs in osteoarthritic chondrocytes. Similar regulatory events had been reported for Galectin-3 and MMP-1 and MMP-9 in murine B16F10 melanoma cells and for MMP-9 in corneal keratinocytes (42)(43)(44), for MMP-7 upregulation by Galectin-7 in murine and human lymphoma cells, and for coexpression of Galectin-7 and MMP-9 in sections of human laryngeal cancer (45,46). In this context, our finding of enhanced bioavailability of effectors of degeneration prompted us to perform transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 70%
“…These results, on the levels of production of mRNA and protein, pinpoint Galectin-1 as a potent inducer of extracellular presence of MMPs in osteoarthritic chondrocytes. Similar regulatory events had been reported for Galectin-3 and MMP-1 and MMP-9 in murine B16F10 melanoma cells and for MMP-9 in corneal keratinocytes (42)(43)(44), for MMP-7 upregulation by Galectin-7 in murine and human lymphoma cells, and for coexpression of Galectin-7 and MMP-9 in sections of human laryngeal cancer (45,46). In this context, our finding of enhanced bioavailability of effectors of degeneration prompted us to perform transcriptomic analyses.…”
Section: Discussionsupporting
confidence: 70%
“…Transfection of galectin-7 cDNA in lymphoma cells of murine model showed significant difference in lymphoma growth rate as indicated by survival mean time of mice as compared to control mice (Demers et al, 2005). On the other hand, galectin-7 transfected 267 T lymphoma cells showed no significant differences in growth rate in comparison of control cells.…”
Section: Galectin-7 In Lymphomasmentioning
confidence: 82%
“…Inhibiting MMP-2 and MMP-9 expression has also been demonstrated to mediate the anti-invasive effects of curcumin (a natural polyphenolic compound) in OSCC cells (24). In line with its pro-invasive activity, galectin-7 expression increases the expression of MMP-9 in several cancer cells (12,16,21). The current study investigated the effects of MMP-2 and MMP-9 on galectin-7 action in OSCC cells.…”
Section: Discussionmentioning
confidence: 95%
“…Galectin-7 exhibits the ability to modulate the metastatic phenotype of several types of cancer cells (10,12,21). Demers et al (21) demonstrated that ectopic expression of galectin-7 increases the invasiveness of lymphoma, accelerates the development of thymic lymphoma, and previously identified that overexpressing galectin-7 enhances the metastatic growth of breast cancer cells in the lungs and bones in two different mouse models (10). Enforced expression of galectin-7 also promotes the invasiveness of human HeLa cervical epithelial adenocarcinoma cells (12).…”
Section: Discussionmentioning
confidence: 99%